Comparison of substance use, subjective well-being and interpersonal relationships among young people in foster care and private households: a cross sectional analysis of the School Health Research Network survey in Wales. Issue 2 (20th February 2017) - Long, Sara Jayne; Evans, Rhiannon E; Fletcher, Adam; Hewitt, Gillian; Murphy, Simon; Young, Honor; Moore, Graham F
Abstract : Objective: To investigate the association of living in foster care (FC) with substance use and subjective well-being in a sample of secondary school students (11–16 years) in Wales in 2015/16, and to examine whether these associations are attenuated by the perceived quality of interpersonal relationships. Design: Cross-sectional, population-based health behaviour and lifestyle questionnaire. Setting and participants: Wales, UK; young people who took part in the 2015/16 School Health Research Network (SHRN) questionnaire (n=32 479). Primary outcome: Health behaviours among young people in FC were compared with those from private households. Results: The prevalence of all adverse outcomes was higher among young people in FC. Those in FC were significantly more likely to report mephedrone use (OR=9.24, 95% CI 5.60 to 15.34), multiple substance misuse behaviours (OR=3.72, 95% CI 2.30 to 6.00), poorer relationships with peers (RR=1.88, 95% CI 1.23 to 2.88) and teachers (RR=1.83, 95% CI 1.31 to 2.56), having experienced bullying (OR=1.80, 95% CI 1.38 to 2.35), dating violence (OR=1.66, 95% CI 1.13 to 2.43) and poor well-being (RR=1.72, 95% CI 1.20 to 2.46). The association between FC and substance use remained significant, though was attenuated after accounting for relationship variables. The association between FC and subjective well-being became non-significant after adjustment for relationship variables. Conclusions: Young people living in FC experience significantly worse outcomes than young people not in care, likely due to a range of care and precare factors, which impact adversely on subsequent social relationships. The analyses are consistent with the hypothesis that the associations of FC with substance use and life satisfaction are partially explained by poorer quality social relationships. Large scale, longitudinal studies are required to investigate the relationship between being in care and health, educational and social outcomes. Mental health interventions and interventions to reduce substance use and improve well-being in FC should include a focus on supporting healthy social relationships.